Mycobacterium tuberculosis – mediated modulation of host macrophage metabolism in the granuloma microenvironment - Kiran, Dilara, author; Basaraba, Randall, advisor; Podell, Brendan, committee member; Obregon-Henao, Andres, committee member; Olver, Christine, committee member; Chicco, Adam, committee member (Colorado State University. Libraries, 2020)
Mycobacterium tuberculosis (Mtb) is the leading cause of death by an infectious agent, and tuberculosis (TB) disease continues to be a prominent global health concern. Infection with Mtb incites granulomatous inflammation, chronic antigen stimulation, and the development of granuloma lesions. These lesions compress tissue architecture in a way that reduces blood supply and creates central regions of hypoxia. Complex lesion pathology, multi-drug resistance of Mtb, co-morbidities with other endemic diseases, the lack of an effective vaccine, and slow drug development pipelines have hindered progress in the field. Researchers have worked to combat these difficulties through their exploration of host-directed therapeutic strategies, which aim to better equip the host immune system to respond to Mtb infection, with a focus on immunometabolism as a target pathway. The metabolism of host macrophages plays a role in modulating disease pathogenesis, with a metabolic switch from oxidative phosphorylation to glycolysis characterizing Mtb infected macrophages. This metabolic switch is primarily regulated at the transcriptional level by hypoxia inducible factor-1α (HIF-1α), which regulates the cellular response to hypoxic stressors encountered within the chronic granuloma lesion microenvironment. Downstream impacts of HIF-1α activation include increased glycolysis, increased lactate production, and increased lactate transport. HIF-1α becomes stable and undergoes its transcriptional activity in conditions of low oxygen, as a result of prolyl hydroxylase (PHD) inhibition. Additionally, hypoxia-independent factors interfere with PHD leading to HIF-1α stabilization, including iron chelation. Bacteria, such as Mtb, have developed iron chelating siderophores to sequester iron from host cells, and knocking-out these iron chelators has been demonstrated to reduce stable HIF-1α activation. As a result, we hypothesized that the Mtb siderophore, mycobactin, plays a role in driving stabilization of HIF-1α during early infection, prior to the development of hypoxic lesion microenvironments. This would serve as a pathogen-driven mechanism that would support macrophage adaptation to hypoxia later during disease progression, and thus develop an Mtb survival niche. Using purified iron chelators deferoxamine (DFO) and mycobactin J (MbtJ), we demonstrated that treated CD1 mouse bone marrow derived macrophages (BMDMs) increase HIF-1α via Western Blot and potently increase glycolytic metabolism as demonstrated by Seahorse Extracellular Flux Analysis. Additionally, the use of mycobactin synthase K (mbtK) knock-out, complement, or wild-type H37Rv strains of Mtb demonstrated the role that mycobactin plays in the metabolic response of macrophages in vitro, having a significant impact on oxidative metabolism. Hypoxia-independent mechanisms of HIF-1α activation by mycobactin may be a critical pathway through which Mtb drives macrophages toward a phenotype conducive for bacterial survival. Lactate produced as a result of increased glycolytic metabolism during infection may also play an important role as a metabolic intermediate and as a signaling molecule during Mtb infection. Metabolic symbioses exist in multiple systems between highly glycolytic, hypoxic cells and more oxidative, normoxic cells, wherein glycolytic cells uptake glucose, convert glucose to lactate via lactate dehydrogenase (LDHA) and export lactate in large amounts via monocarboxylate transporter 4 (MCT4). Normoxic cells import lactate via monocarboxylate transporter 1 (MCT1) and convert it back to pyruvate via lactate dehydrogenase B (LDHB) and utilize lactate-derived pyruvate to fuel mitochondrial respiration. This preserves glucose for hypoxic cells which rely heavily on glycolysis for metabolic survival. While this type of lactate shuttle has been demonstrated to regulate the tumor microenvironment, it has yet to be explored within the context of the similar TB granuloma microenvironment. As a result, we explored the role of a lactate shuttle within Mtb infection by detecting lactate in guinea pig plasma, detecting lactate shuttle components within guinea pig granuloma lesions, and by using the LDHA inhibitor sodium oxamate and the MCT1 inhibitor α-Cyano-4-hydroxycinnamic acid (α-CHC), both of which are commercially available. We showed that Mtb infection significantly increases lactate on both a systemic and cellular level. We successfully demonstrated that LDH and MCT inhibition augments metabolism in macrophages by blocking glycolysis and decreasing mitochondrial spare capacity. Through in vitro Mtb infection models, we were able to show that inhibitor treatment can reduce the amount of lactate accumulated. These studies demonstrated proof of concept for the role of a lactate shuttle in modulating macrophage metabolism during Mtb infection and maintaining infection dynamics within the granuloma microenvironment. Overall, the research presented herein seeks to understand the ways in which Mtb infection drives host macrophages to alter their metabolic phenotype in a way that promotes Mtb survival and contributes to disease pathogenesis. A better understanding of the interactions which occur at the host-pathogen interface will provide important insight for the development of host-directed therapeutic strategies which will better equip host cells to combat Mtb infection.
Keywords: mycobacteria; metabolism; tuberculosis